A retrospective cohort study of fetal assessment following preterm premature rupture of membranes. Issue 1 (19th February 2019) - Tepper, Jared; Corelli, Kathryn; Navathe, Reshama; Smith, Stephen; Baxter, Jason K.
Abstract: Objective: To evaluate maternal and neonatal outcomes following management of preterm premature rupture of membranes (PPROM) by two fetal assessment strategies. Methods: In a retrospective cohort study performed at two hospitals in Philadelphia, Pennsylvania between July 2010 and June 2015, data were reviewed from 180 singleton pregnancies with PPROM at 23 0 –33 6  weeks of gestation that underwent expectant management. Outcomes were compared between continuous electronic fetal heart monitoring (EFM) with daily biophysical profile (BPP) ("continuous monitoring") and non‐stress test (NST) three times per day ("periodic monitoring") using Mann‐Whitney U and Fisher exact tests. Results: Overall, 119 (66.1%) pregnancies were assessed by continuous monitoring and 61 (33.9%) by periodic monitoring. There was no difference in frequency of intrauterine death between the continuous monitoring (1, 0.8%) and periodic monitoring (3, 4.9%) groups (OR, 0.16; 95% CI, 0.02–1.61). The continuous monitoring group was more likely to have an interventional (OR, 2.17; 95% CI, 1.06–4.44) or cesarean (OR 3.30, 95% CI 1.70–6.38) delivery. Conclusion: Continuous EFM with daily BPP was associated with higher rates of intervention and cesarean delivery compared with periodic NST, but there was no difference in intrauterine or perinatal mortality. Abstract : Continuous monitoring resulted in higher frequencies of interventional delivery, cesarean, and neonatal respiratory distress syndrome, but did not reduce intrauterine fetal demise or perinatal death.